2010
DOI: 10.1111/j.1365-2427.2010.02480.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coalbed natural gas development on fish assemblages in tributary streams of the Powder and Tongue rivers

Abstract: 1. Extraction of coalbed natural gas (CBNG) often results in disposal of large quantities of CBNG product water, which may affect aquatic ecosystems. We evaluated the effects of CBNG development on fish assemblages in tributary streams of the Powder and Tongue rivers. We used treatment and control, impact versus reference sites comparisons, surveys of CBNG product-water streams and in situ fish survival approaches to determine if CBNG development affected fish assemblages. 2. Several of our results suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 33 publications
0
28
1
Order By: Relevance
“…Species codes are first letter of genus then first four letters of specific epithet. By contrast, Davis et al (2010) found negative relations between number of gas wells and gas well density in the upstream catchment and native species richness, catostomid and ictalurid richness, number of long-lived species and familial richness. Tongue rivers, Montana-Wyoming, USA.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Species codes are first letter of genus then first four letters of specific epithet. By contrast, Davis et al (2010) found negative relations between number of gas wells and gas well density in the upstream catchment and native species richness, catostomid and ictalurid richness, number of long-lived species and familial richness. Tongue rivers, Montana-Wyoming, USA.…”
Section: Discussioncontrasting
confidence: 56%
“…Davis et al (2010) found no significant differences in fish assemblage structure metrics between coal-bed natural gas development sites and control sites in tributaries to the Powder and Figure 5. Davis et al (2010) found no significant differences in fish assemblage structure metrics between coal-bed natural gas development sites and control sites in tributaries to the Powder and Figure 5.…”
Section: Discussionmentioning
confidence: 81%
“…Such activities, including large-scale construction, massive hydraulic fracturing and horizontal drilling, have expanded in the continental United States to access previously inaccessible natural gas reservoirs for rising energy demands (Davis et al 2010;Entrekin et al 2011). Including changes to water chemistry and deforestation, siltation is expected to be a particularly detrimental effect of NNGE activities (Williams et al 2008;Davis et al 2010;Entrekin et al 2011). Development in the Fayetteville Shale in the eastern portion of the range of E. whipplei, as in most shale-gas basins, has been extremely recent and rapid, and the effects of NNGE activities to stream biota are not currently well understood (Entrekin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Shepard et al (1993) found an overall decline of Gulf darters (Etheostoma swaini) and an increase of rough shiners (Notropis baileyi) in the presence of product water in the Black Warrior system. Davis et al (2010) focused on coarse-scale community metrics (e.g., Indices of Biotic Integrity), and at this scale had difficulty elucidating shifts in fish community composition, but did find that many ephemeral streams currently experiencing sustained treated product water outflow were capable of supporting fishes. Compounding the difficulties faced by Davis et al (2010) is that their work was conducted on fishes in streams of the North American Great Plains ecoregion, where many species are known for being physiologically tolerant to such disturbances as rapid changes in temperature, salinity, and dissolved oxygen (Dodds et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation